Caracterização de compostos bioativos em germoplasma de milho e aplicação em biopolímeros alimentícios - Barbosa, Natália Alves (2016)
Corn has wide genetic diversity, originating a large numbers of varieties and hybrids. This crop shows several colorations of grains, however, colored corns, such as red, purple, blue and black, are commercially produced only in small quantities, despite presenting substances with potential for the development of functional foods. In this thesis, the proposal was to characterize some tropical maize belonging to the Embrapa Milho e Sorgo Germplasm Bank in relation to the composition of substances of nutritional and industrial importance in the grains, to select access of higher concentration of phytochemicals and antioxidant activity, besides obtaining phenolic extract with high antioxidant activity for the incorporation in biopolymer with antimicrobial action and application in the extension of the useful life of strawberries stored under refrigeration, covered by this biopolymer. Therefore, the thesis is divided into five chapters. It was concluded that maizes from the active colored tropical corn germplasm bank shows difference in the composition of phenolic, anthocyanin and antioxidant capacity of the grain, and these are in higher concentrations in grains with more intense color (Chapter 2); among genotypes what stands out most about the composition of phytochemicals and antioxidant capacity is the TO 002 (Chapter 3); to obtain a phenolic extract is ideal to work with a temperature of 20 ° C and 80% ethanol solvent and edible biopolymers based on starch and zein with addition of 100% corn TO statement 002 has antimicrobial activity against Staphylococcus aureus bacteria (Chapter 4) and strawberries stored in coated cooling starch coverage or zein added to 100% of phenolic extract they may have longer life than non-coated strawberries (Chapter 5).